Analysis of EMSE and mechanical properties of sputter coated electrospun nanofibers - SANCAK, ERHAN (ELSEVIER SCIENCE BV, 2016)
PA6 nanofibers were electrospun successfully and sputter coated with gold and palladium to create functional nanofibrous membranes that possess electromagnetic shielding ability. Properties of the electrospinning solutions were analyzed in terms of viscosity, conductivity and pH values. Coating thicknesses of the nanofibrous membranes were determined as 50 nm and 100 nm. Morphology of the nanofibrous membranes were observed by SEM analysis. Elemental composition of the specimens was explored by using Energy Dispersive Spectroscopy. Results revealed that defect free and uniform nanofibers were obtained, and the diameters of the fibers were changed after coating. Tensile strength and elongation measurements confirmed that the mechanical characteristics of the nanofibrous membranes were merely altered after coating. Electromagnetic Shielding Effectiveness (EMSE) of the nanofibers was determined according to the ASTM D4935-10 protocol by using coaxial transmission line measurement technique in the frequency range of 15-3000 MHz. It was observed that 100 nm coated membrane performed better EMSE than uncoated and 50 nm coated nanofibrous membranes. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Electrospinning; Nanofibrous membrane; Polyamide 6; Sputter coating; Electromagnetic shielding effectiveness; POLYMER NANOFIBERS; FIBERS